INNOVATIVE STRATEGIES OF LANGUAGE TEACHING IN THE CONTEXT OF GLOBALIZATION (Modern education and development, 2025)
Globalization has transformed language education, necessitating innovative teaching strategies that prepare learners for effective communication in a rapidly interconnected world. This study explores modern approaches such as technology-assisted learning, task-based instruction, intercultural competence training, and multilingual education. It evaluates how these strategies improve language proficiency, engagement, and adaptability in diverse linguistic environments. The research employs a mixed-method design, incorporating literature review, classroom observations, and surveys to assess the effectiveness of innovative techniques. Findings indicate that blended learning, gamification, and communicative approaches significantly enhance language acquisition and real-world applicability. The study concludes that adapting language education to globalization trends is essential for developing 21st-century communication skills.